Improving Service Levels in the Hotel Industry through a Lean Service Model: A Case Study - Quiroz-Flores, Juan Carlos; Ampuero-Rodas, Ana; Palma-Farfan, Jordana (LACCEI, 2024)
Companies in the hotel sector aim to offer a high level of service to their customers. However, factors such as cleanliness and customer service make it challenging to obtain the expected results. For this reason, an operations model was developed that combines Lean tools such as 5S, Poka Yoke, and standardized work tools to increase customer satisfaction in a hotel in Cuzco, Peru. The results obtained from implementing the model through a pilot test and a simulation test using Arena software proved the model's performance since the Satisfaction Level increased from 78.48 to 80.13 and the Net Promoter Score from 24.22% to 33.22%. This research concludes that the proposal increases the satisfaction of the company’s customers, which translates into higher revenues. It is also significant in providing valuable information for the hotel and tourism sector in Peru, thus contributing to improving the quality and competitiveness of the sector